2015
DOI: 10.1001/jamasurg.2015.0306
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin for Gastric Emptying in Patients Undergoing General Anesthesia for Emergency Surgery

Abstract: ClinicalTrials.gov identifier: NCT00827216.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 56 publications
0
21
1
2
Order By: Relevance
“…19 Despite the controversy of the cellular mechanism of prokinetic & other effects of erythromycin on various parts of the gastrointestinal tract in different species, the prokinetic effect of erythromycin is confirmed beyond doubt in humans. [4][5][6][7][8][9][10][11][12][13] In conclusion, the present study shows that erythromycin base has different effects on different parts of the gastrointestinal tract in different species of animals in vitro. The cellular mechanism of effects of erythromycin on various parts of gastrointestinal tract is still not known with certainty.…”
Section: Fig 2a: Erythromycin (Em) 100 and 300 μM Reduced The Magnitudmentioning
confidence: 83%
See 1 more Smart Citation
“…19 Despite the controversy of the cellular mechanism of prokinetic & other effects of erythromycin on various parts of the gastrointestinal tract in different species, the prokinetic effect of erythromycin is confirmed beyond doubt in humans. [4][5][6][7][8][9][10][11][12][13] In conclusion, the present study shows that erythromycin base has different effects on different parts of the gastrointestinal tract in different species of animals in vitro. The cellular mechanism of effects of erythromycin on various parts of gastrointestinal tract is still not known with certainty.…”
Section: Fig 2a: Erythromycin (Em) 100 and 300 μM Reduced The Magnitudmentioning
confidence: 83%
“…3 The prokinetic effect of erythromycin has been reported and confirmed in human volunteers in the fasting and fed state. [4][5][6][7][8] Acute and chronic treatment with erythromycin improves gastric emptying in idiopathic and diabetic gastroparesis 9,10 as well as post vagotomy gastroparesis. 11 It increases the tone of lower oesophageal sphincter and relieves dyspeptic symptoms in patients with gastrooesophageal reflux disease 12,13 and also stimulates gall bladder emptying.…”
mentioning
confidence: 99%
“…Human studies have shown erythromycin can help prevent delayed gastric emptying associated with general anaesthesia and decreases acidity and residual gastric fluid volume (Czarnetzki et al . ). Erythromycin administered at low doses (0·5 to 1 mg/kg three times a day) is not associated with antimicrobial effects (Boothe ).…”
Section: Therapeutic Targetsmentioning
confidence: 97%
“…Дотримання часу передопераційного спожи-вання їжі та пиття рідин дозволяє знизити ризи-ки регургітації та легеневої аспірації шлункового вмісту [1,2]. Для дорослих та дітей опубліковані рекомендації Європейського товариства анестезії (European Society of Anaesthesiology, ESA) та Аме-риканського товариства анестезіологів (American Society of Anesthesiologists, ASA), згідно з якими об-меження передопераційного споживання твердої їжі та сумішей для харчування немовлят (дітей до 1 року) становить 6 годин, грудного молока -4 го-дини, пиття прозорих рідин (вода, сік без м'якоті, чай чи кава без молока) -до 2 годин [3,4].…”
Section: Original Researches оригинальные исследования вступunclassified
“…Дотримання часу передопераційного голодуван-ня є рутинною анестезіологічною практикою для зменшення ризику регургітації та легеневої аспіра-ції [1,2]. На сьогодні емпірично не встановлений об'єм залишкової рідини шлунка, який добре толе-рується пацієнтом та не чинить ризиків аспірації.…”
Section: обговоренняunclassified